Reconstruction of the Integration of Religion and Modern Sanis - Waluyo; Engku Ab Rahman, Ts. Engku Shahrulerizal Bin; Nurkhafiq, M. (Al-Hayat: Journal of Islamic Education, 2025)
The meeting of modern religion and science in the 17th century, although the initial encounter seemed to be a distinct entity from philosophical and historical perspectives, was once mutually coordinated. Different paradigms of religion and science are the background of this study. This paper focuses on efforts to reconceptualise and to reconstruct the integration of Islamic education interconnections (integration of religion and science). The research was inspired by a book entitled “Merumuskan Rangka Kerja Islamisasi Ilmu Pengetahuan: Islamisasi Worldview, Paradigma dan Teori," which contains a literature study on the Islamization of science, utilising hermeneutical research methods. Data analysis refers to the description of the data, and then a synthesis analysis is carried out. The modern model of integrating religion and science does not mean the fusion of two entities into one, nor does it involve one merging with the other. The findings of integration and interconnection were obtained by reconstructing the curriculum through its integration with the Qur'an. Unlike previous models of the Islamization of science, which employed a merging model, this research focuses more on the integration with the Qur'an, rather than discussing the objects and objects being Islamized. The process of integrating it into the curriculum begins with the development of a preparation program for educators to integrate faith and science. Finally, the writing seeks to add a new dimension to the integration of religion and science, where the essence of both (religion and science) lies in the concept of monotheism (faith).